2022
DOI: 10.3390/v14112472
|View full text |Cite
|
Sign up to set email alerts
|

HTLV-2 Enhances CD8+ T Cell-Mediated HIV-1 Inhibition and Reduces HIV-1 Integrated Proviral Load in People Living with HIV-1

Abstract: People living with HIV-1 and HTLV-2 concomitantly show slower CD4+ T cell depletion and AIDS progression, more frequency of the natural control of HIV-1, and lower mortality rates. A similar beneficial effect of this infection has been reported on HCV coinfection reducing transaminases, increasing the spontaneous clearance of HCV infection and delaying the development of hepatic fibrosis. Given the critical role of CD8+ T cells in controlling HIV-1 infection, we analysed the role of CD8+ T cell-mediated cytoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…Also, HIV-1 proviral load is associated with HTLV-2 infection. The authors confirmed and expanded previous findings on the role of HTLV-2 in the beneficial effect on the pathogenesis of HIV-1 in coinfected individuals [1].…”
supporting
confidence: 86%
“…Also, HIV-1 proviral load is associated with HTLV-2 infection. The authors confirmed and expanded previous findings on the role of HTLV-2 in the beneficial effect on the pathogenesis of HIV-1 in coinfected individuals [1].…”
supporting
confidence: 86%
“…In contrast, coinfection of HIV with HTLV-2, another type of HTLV that is non-pathogenic but rarely associated with HAM/TSP, showed slow T cell depletion and AIDS progression, with higher HIV-1 viral control and lower mortality rates [79]. This effect is mediated via CTL expansion induced by HTLV-2, including a high rate of the effector memory phenotype and increased levels of granzymes A and B and perforin [79]. Although a case of ATL in an HIV-1-positive patient has been reported A B [80], more evidence is needed to determine the possibility of patients with HIV having an increased risk of ATL.…”
Section: Hivmentioning
confidence: 95%
“…HTLV-1 activates CD4+ T cells, and Tax upregulates HIV-1 infection [78]. In contrast, coinfection of HIV with HTLV-2, another type of HTLV that is non-pathogenic but rarely associated with HAM/TSP, showed slow T cell depletion and AIDS progression, with higher HIV-1 viral control and lower mortality rates [79]. This effect is mediated via CTL expansion induced by HTLV-2, including a high rate of the effector memory phenotype and increased levels of granzymes A and B and perforin [79].…”
Section: Hivmentioning
confidence: 99%
“…HTLV-1 activates CD4+ T cells, and Tax upregulates HIV-1 infection [78]. In contrast, HIV coinfection with HTLV-2, another type of HTLV that is non-pathogenic but rarely associated with HAM/TSP, is associated with slow T-cell depletion and AIDS progression, with higher HIV-1 viral control and lower mortality rates [79]. This effect is mediated by CTL expansion induced by HTLV-2, including a high rate of the effector memory phenotype and increased levels of granzymes A and B and perforin [79].…”
Section: Coinfection 421 Hivmentioning
confidence: 99%
“…In contrast, HIV coinfection with HTLV-2, another type of HTLV that is non-pathogenic but rarely associated with HAM/TSP, is associated with slow T-cell depletion and AIDS progression, with higher HIV-1 viral control and lower mortality rates [79]. This effect is mediated by CTL expansion induced by HTLV-2, including a high rate of the effector memory phenotype and increased levels of granzymes A and B and perforin [79]. Although a case of ATL has been reported in an HIV-1-positive patient [80], more evidence is needed to determine whether individuals with HIV infection have an increased risk of ATL.…”
Section: Coinfection 421 Hivmentioning
confidence: 99%